2020
DOI: 10.1111/mmi.14455
|View full text |Cite
|
Sign up to set email alerts
|

Galactosylated wall teichoic acid, but not lipoteichoic acid, retains InlB on the surface of serovar 4b Listeria monocytogenes

Abstract: Listeria monocytogenes is a Gram‐positive, intracellular pathogen harboring the surface‐associated virulence factor InlB, which enables entry into certain host cells. Structurally diverse wall teichoic acids (WTAs), which can also be differentially glycosylated, determine the antigenic basis of the various Listeria serovars. WTAs have many physiological functions; they can serve as receptors for bacteriophages, and provide a substrate for binding of surface proteins such as InlB. In contrast, the membrane‐anch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 72 publications
(144 reference statements)
1
22
0
Order By: Relevance
“…To identify suitable phage RBPs for complementing the glycotyping scheme, putative baseplate-associated proteins of various Listeria phages with distinct host ranges were subjected to in silico analyses using HHpred (38), BLASTp (39), and Jpred secondary structure predictions (40). Based on the conserved synteny of Listeria siphoviral structural genes (23), four tail spike RBPs from bacteriophages A006 (gp17), A500 (gp19) (16), PSA (gp15) (41), and B025 (gp18) were selected to expand the repertoire of GFP-tagged phage proteins, aiming at SV-specific glycotype identification. We produced and purified recombinant His-tagged versions of these proteins (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify suitable phage RBPs for complementing the glycotyping scheme, putative baseplate-associated proteins of various Listeria phages with distinct host ranges were subjected to in silico analyses using HHpred (38), BLASTp (39), and Jpred secondary structure predictions (40). Based on the conserved synteny of Listeria siphoviral structural genes (23), four tail spike RBPs from bacteriophages A006 (gp17), A500 (gp19) (16), PSA (gp15) (41), and B025 (gp18) were selected to expand the repertoire of GFP-tagged phage proteins, aiming at SV-specific glycotype identification. We produced and purified recombinant His-tagged versions of these proteins (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The pB025_gp18-GFP vector was created by inserting a gfp followed by a SacI restriction site between the NdeI and BamHI restriction sites of the pET302 NT-His vector (Invitrogen, Carlsbad, CA, USA); subsequently, a commercially ordered DNA fragment of the full-length B025_gp18 sequence (GeneArt; Thermo Fisher Scientific, Waltham, USA) was inserted between SacI and BamHI, as previously described (36). The pA500_gp19-GFP vector was created by ligating the full-length A500_gp19 sequence (amplified by primers A500_gp19-F/R from whole purified phage) into the SacI-SalI restriction sites of the pHGFP vector (16,37). The pA006_gp17-biotin vector was created by inserting the truncated A006_gp17 sequence (amplified from whole A006 phage) via Gibson assembly (69) into the p165-His/Avi-tagged vector.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that autolysins that possess such GW domains mediate their surface presentation through direct binding to glycosylated WTAs (Cabanes, Dussurget, Dehoux, & Cossart, 2004). WTA rhamnosylation in an SV 1/2a background, and galactosylation in a 4b strain were shown to be responsible for retaining and displaying InlB (Carvalho, Sousa, & Cabanes, 2018;Sumrall et al, 2019;Sumrall et al, 2020). Previously, LTA had also been implicated as the binding partner for GW-domain containing proteins (Jonquieres, Bierne, Fiedler, Gounon, & Cossart, 1999).…”
Section: The Role Of Tas In Physiology and Pathogenesismentioning
confidence: 99%
“…Such knowledge allows the construction of mutants with specifically modified TA decoration. Recent studies have highlighted the roles of TAs in Listeria physiology, antigenic determination, susceptibility to antibacterials, virulence, and in the interactions between bacteria, bacteriophages and eukaryotic host cells (Abachin et al, 2002;Carvalho et al, 2015;Spears et al, 2016;Sumrall et al, 2019;Sumrall et al, 2020;Yin et al, 2019).…”
mentioning
confidence: 99%